2012
DOI: 10.1111/j.1365-2133.2012.11002.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre- vs. post-pubertal onset of vitiligo: multivariate analysis indicates atopic diathesis association in pre-pubertal onset vitiligo

Abstract: Pre-pubertal onset vitiligo is strongly associated with personal and family history of atopy, suggesting that the predisposing immune background in vitiligo is not limited to autoimmunity, as also noted in alopecia areata. This study also suggests reconsidering the epidemiological data on sex ratio in vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 34 publications
1
52
1
1
Order By: Relevance
“…10 AITD can be associated (clinical autoimmune thyroiditis) or not (subclinical autoimmune thyroiditis) with thyroid dysfunction. [13][14][15] Despite this positive association, few reports have been aimed at identifying weighted factors associated with AITD in patients with vitiligo ⁄NSV using logistic regression procedures. 11 The prevalence of anti-TPO antibodies has been found to be higher in patients with vitiligo compared with patients without vitiligo 12 and anti-TPO antibodies were found to be present in 4AE4-21% of patients with vitiligo.…”
mentioning
confidence: 99%
“…10 AITD can be associated (clinical autoimmune thyroiditis) or not (subclinical autoimmune thyroiditis) with thyroid dysfunction. [13][14][15] Despite this positive association, few reports have been aimed at identifying weighted factors associated with AITD in patients with vitiligo ⁄NSV using logistic regression procedures. 11 The prevalence of anti-TPO antibodies has been found to be higher in patients with vitiligo compared with patients without vitiligo 12 and anti-TPO antibodies were found to be present in 4AE4-21% of patients with vitiligo.…”
mentioning
confidence: 99%
“…In IFNE, type I IFN receptors may be affected by progesterone and the signal may differ (Hughes, 2011). However, in previous study, pre-and post-pubertal onset vitiligo was not significantly different by gender (Ezzedine et al, 2012), and significance in Table 4 is only slight different from Table 3. Therefore this also needs confirmation in larger samples.…”
Section: Discussionmentioning
confidence: 68%
“…It has been suggested that pre-pubertal onset of vitiligo is strongly associated with a genetic background, that adult onset vitiligo is more linked to autoimmunity (Ezzedine et al, 2012), and that autoimmune diseases are affected by sex hormones (Hughes, 2011;McCombe et al, 2009). In IFNE, type I IFN receptors may be affected by progesterone and the signal may differ (Hughes, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Dear Editor , Vitiligo is a depigmenting skin disorder with an estimated prevalence of 1% . Childhood‐onset vitiligo occurs in approximately one‐third of all cases . Early‐onset childhood vitiligo tends to be a more extensive and progressive type of vitiligo .…”
Section: Descriptive Data Of the Respondentsmentioning
confidence: 99%